A revolução francesa de Ernest Hemingway - Souza Júnior, Luís Roberto de (2017)
This thesis retells and reinterprets, from a historic and literary point of view, the initial period (1922-1925) in which Ernest Hemingway lived in Paris and how he modeled his apprenticeship and forged a revolutionary style of writing prose. The main support of the thesis is the analysis of the recently published letters of the author: the first volume (2011), encompassing the years 1907-1922, and the second volume (2013), covering 1923–1925. The guiding question drives to the mechanisms that made possible Hemingway to consolidate himself as an artist and create a literary revolution. Furthermore, it aims to verify if Hemingway, in the letters, seemed to be the same brutal man whose image he wanted to cultivate. The structure of the thesis has three parts. The first part, “The Pre-revolutionary Period”, is a sort of radiography of modernist Paris, when the city acted as a magnet for a international range of artists, creating a culture of cross-fertilisation. The theoretical pillars are Malcolm Bradbury's studies about Modernism and Antonio Candido's ideas on how a stimulating milieu helps literary creation. The second part is entitled "The Revolution" and corresponds to the core of the thesis. Using his letters as the primary source of information, the system of relation and literary exchange experienced by Hemingway is examined in detail. The third part, The Post-Revolutionary Period, investigates the posthumous book of “fictional memories” Paris a Moveable Feast, showing its troubled composition. It’s also made a comparison between the first version (1964) and the restored edition (2009), including a number of never-before-published material. The Final Consideration confirms that Paris’ cultural and literary ambiance transformed Hemingway and certifies that he was a complex man, far from his one-sided public image.